Evaluating the Assessment Rubrics of an English Course - Herdiawan, Rama Dwika (Universitas Negeri Semarang, 2017)
Evaluation needs to be conducted regularly in order to assist the institution enhance its own performance management. Thus, this study is focused on evaluating the assessment of questionnaire rubrics used by National English Course (NEC) based on the evaluation rubrics proposed by Marshall (2014) which were concerned with the four-rating scales and the six domains covering the whole aspects of lecturers‘ performances. They are planning and preparation for Learning, classroom management, delivery of Instruction, monitoring, Assessment, and follow-up, and professional responsibilities. The data gained from the lecturers‘ interview revealed that the NEC lecturers used some domains which contained aspects of lecturer‘s performance but not all aspects used in reality. Basically, they had considered the five domains of the rubric. However, few aspects were used in each domain, for example: in domain of planning and preparation; they only used aspects of knowledge, lessons, and also engagement. It needs further revision dealing with the assessment or evaluation on teacher‘s performance, materials, and so on. Meanwhile, the data gained from document observation revealed that the content of questionnaire did not cover all the aspects for the whole domains. It only covers some domains such as planning and preparation for Learning, and classroom management. This study indicated that providing the relevant aspects as well as the rating scale in the questionnaire is needed to be used in terms of teacher‘s evaluation rubric.